2020
DOI: 10.3389/fpsyt.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in the Treatment of Schizophrenia

Abstract: Background: Inflammation plays a major role in the onset and maintenance of schizophrenia. The objective of the present work was to synthetize in a narrative review the recent findings in the field of inflammation in schizophrenia and their application in daily practice. Method:This review was based on the most recent meta-analyses and randomized controlled trials. Results:The disturbed cytokines depend on the phase of the illness. A meta-analysis of cytokines in schizophrenia found higher levels of pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 41 publications
2
70
0
1
Order By: Relevance
“…Indeed, some antioxidants such as vitamins and essential polyunsaturated fatty acids have been shown to ameliorate the symptoms of schizophrenia [ 144 , 145 , 146 ]. Moreover, several studies have reported that schizophrenia can be treated with a combination of dietary supplementation, adjuvant antioxidant therapy, and antipsychotic medication [ 147 , 148 ].…”
Section: Positive Effects Of Nutraceuticals and Antioxidants On Scmentioning
confidence: 99%
“…Indeed, some antioxidants such as vitamins and essential polyunsaturated fatty acids have been shown to ameliorate the symptoms of schizophrenia [ 144 , 145 , 146 ]. Moreover, several studies have reported that schizophrenia can be treated with a combination of dietary supplementation, adjuvant antioxidant therapy, and antipsychotic medication [ 147 , 148 ].…”
Section: Positive Effects Of Nutraceuticals and Antioxidants On Scmentioning
confidence: 99%
“…In the central nervous system (CNS), inflammation may be neuroprotective or neurotoxic depending on the interactions among genetic variations, environmental factors, and inflammatory responses [ 17 ]. Recent evidence regarding inflammation and schizophrenia suggests that inflammation is a possible risk factor to induce schizophrenia and to aggravate its symptoms [ 16 18 19 20 ]. The levels of pro-inflammatory cytokines including interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-1β, IL-12, and transforming growth factor (TGF)-β were elevated in subjects with schizophrenia [ 21 22 ].…”
Section: Inflammation and Schizophreniamentioning
confidence: 99%
“…During the last 50 years, clinical neuroimaging and molecular studies suggest that immune dysfunction is one of the factors contributing to the pathogenesis of schizophrenia. 56 , 57 Mounting evidence shows that inflammation has a potential role in the development and maintenance of the disease 58–61 and immune and inflammatory mediators could serve as potential biomarkers for schizophrenia. 1 , 62 One hypothesis is that immune alterations observed in the CNS could originate from changes in the peripheral immune system.…”
Section: Discussionmentioning
confidence: 99%